Prenatal ultrasonographic markers for prediction of complex gastroschisis and adverse perinatal outcomes: a systematic review and meta-analysis. Issue 4 (4th October 2021) - Sun, Raphael C; Hessami, Kamran; Krispin, Eyal; Pammi, Mohan; Mostafaei, Shayan; Joyeux, Luc; Deprest, Jan; Keswani, Sundeep; Lee, Timothy C; King, Alice; Belfort, Michael A; Shamshirsaz, Alireza A
Abstract : Objective: We sought to perform a meta-analysis of the predictive value of antenatal ultrasonographic markers of bowel dilation, gastric dilation, polyhydramnios and abdominal circumference that predict complex gastroschisis and adverse perinatal outcomes Data sources: PubMed, Web of Science, Scopus and Embase were searched for relevant articles up to December 2020. Studies reporting prenatal ultrasonographic markers including intra-abdominal bowel dilation (IABD), extra-abdominal bowel dilation (EABD), bowel wall thickness, polyhydramnios, abdominal circumference <5th percentile, gastric dilation (GD) and bowel dilation not otherwise specified (BD-NOS) were included. The primary outcome was prediction of complex gastroschisis; secondary outcomes were length of hospital stay for newborn, time to full enteral feeding, postnatal mortality rate, incidence of necrotising enterocolitis and short bowel syndrome. Results: Thirty-six studies were included in this meta-analysis. We found significant associations between complex gastroschisis and IABD (OR=5.42; 95% CI 3.24 to 9.06), EABD (OR=2.27; 95% CI 1.40 to 3.66), BD-NOS (OR=6.27; 95% CI 1.97 to 19.97), GD (OR=1.88; 95% CI 1.22 to 2.92) and polyhydramnios (OR=6.93; 95% CI 3.39 to 14.18). Second trimester IABD and EABD have greater specificity for the prediction of complex gastroschisis than third trimester values with specificity of 95.6% (95% CI 58.1 to 99.7) and 94.6% (95% CI 86.7 to 97.9) for the second trimester IABD and EABD, respectively. Conclusion: Prenatal ultrasonographic markers, especially the second trimester IABD and EABD, can identify fetuses that develop complex gastroschisis. Furthermore, these specific ultrasonographic markers can identify those babies at the highest risk for severe complications of this congenital anomaly and hence selected for future antenatal interventions. Abstract : Based on a systematic review, it was concluded that observed bowel dilatation in the second trimester of pregnancy was significantly associated with the development of complex gastroschisis, postnatal short bowel syndrome and length of stay.